PENGARUH BIMBINGAN BELAJAR OLEH KELOMPOK SOSIAL KHATULISTIWA BERBAGI TERHADAP PRESTASI BELAJAR ANAK MARJINAL - Rahmatika, Dwi Bintang; Zakso, Amrazi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research entitled the influence of tutoring by Khatulistiwa Berbagi Social groups on the learning achievements of marginal children in the area of Komplek Waduk Permai Pontianak. This research purpose to find out the influence of tutoring on the learning achievements of marginal children, with the general problem is "How the influence of tutoring by Khatulistiwa Berbagi Social groups on the learning achievement of marginal children of Komplek Waduk Permai Pontianak area" is quantitative with the research subjects of 58 marginal children selected from 67 marginal children using sample random sampling method. Data collection techniques are indirect communication techniques and documentation techniques, data collection tools are questionnaires and archives. The results obtained showed the influence of tutoring by Khatulistiwa Berbagi Social groups by 68% and the learning achievement of marginal children of Komplek Waduk Permai Pontianak area is 84.5%, both are in the high category. The result of hypothesis testing shows that there is a positive and significant influence between tutoring and marginal student learning achievement with rCount bigger than rTable (0.845> 0.254) and Sig value. smaller than Alpha (Î±) (0.00 <0.05). Regression equation Y = 14,090 + 0,873 X showed that if tutoring increase one, hence learning achievement increase equal to 0,873. Adjusted determinant value R2 = 0.708 which means the influence of tutoring on learning achievement is 70.8% and 29.2% the rest is influenced by other factors.Keywords: Tutoring, Khatulistiwa Berbagi, Learning Achievement, Marginal